Consolidation of healthcare centres (ZOZ) in the Lublin area - Książek, Piot; Okoński, Piotr; Kamiński, Maciej; Warchoł-Sławińska, Ewa; Furtak, Marzena; Włoch, Krzysztof; Drop, Bartłomiej (Polish Journal of Public Health, 2011)
Introduction. The difficult situation in the healthcare requires continuous efforts focused on possibilities of reducing the debts of hospitals. A consolidation of healthcare centres is one of methods of hospitals restructuring. Aim. The aim of this study was describing views of the administrative staff of hospitals, the founding body of which is Marshal Office in Lublin, and of randomly chosen patients on the consolidation of healthcare centres in Lublin. Material and methods. The study use the diagnostic survey which was responded by a total of 71 employees of 4 hospitals subordinated to Marshal Office in Lublin, as well as by 103 patients of Lublin hospitals. Results. The employees of 4 hospitals subordinated to Marshal Office in Lublin, are generally familiar (56%) with the problems of consolidation of ZOZ centres. The attitude of the administrative staff to the consolidation of ZOZ centres is largely negative (66%). Patients, the beneficiares of medicalservices are largely (84%) dissatisfied with the current situation in the health care. Amongst threats which can result from the merger of hospitals, patients distinguish among others worsening of the sense of orientation as for the place of treatment (49%) and longer waiting for admission to the hospital (13%), as well as to the specialist (13%). Discussion. The merger of hospitals is definitely advantageous due to the possibility of quick savings however at the expense of persons of the administrative staff working at these combined hospitals (redundancies). Conclusion. The administrative staff who largely know issues of the consolidation of healthcare centres, are not in favour of the restructuring of this type because of possible job loss, resulting from administrative staff reductions at merged hospitals. Patients of Lublin hospitals, who largely don't know issues of the merger of hospitals, can mainly see positives in the consolidation of healthcare centres (ZOZ). It follows that patients of Lublin hospitals look forward with optimism at restructuring of this type, which can surely be beneficial for them.